Perkembangan Islam pada Masyarakat Banjar dalam Budaya dan Fiqh Tasawuf - Irawan, Andhi; , M.Ag, Dr. H. Sukarni, M.Ag; ,.Hum, Prof. Dr. H. M. Hanafiah; Muhajir, MA, Dr. Ahmad (Sharia Journal and Education Center Publishing, 2024)
Abstract This study examines the development of Islam within the Banjar community, focusing on cultural and Sufi jurisprudence aspects. The Banjar community is a culturally rich society significantly influenced by Islamic traditions. Islamic traditions permeate every stage of life in the Banjar society, manifesting in various life rituals such as childbirth, child-rearing, education, adolescence, marriage preparation, weddings, religious education, illness, and death. Additionally, Islamic traditions are observed during major religious celebrations such as Ramadan, Syawal, Eid al-Adha, and Hajj. The Islamic traditions in the Banjar community have been heavily influenced by Sufi teachings introduced by Islamic scholars from the Middle East. In subsequent stages, several prominent scholars from Banjar traveled to the Middle East to study Islamic sciences and disseminate their knowledge by teaching and publishing books to spread Islamic teachings.One notable Banjar scholar is Sheikh Arsyad Al-Banjari, who realigned Banjar culture with Islamic teachings by prohibiting practices like Sanggar Banua and Membuang Pasilih, which could lead the Banjar community towards transgressions and heretical innovations, including practices involving offerings to spirits. Keywords: Islamic Development, Banjar Community, Cultural Influence, Sufi Jurisprudence, Life Rituals, Islamic Traditions, Middle Eastern Scholars, Sheikh Arsyad Al-Banjari. Abstrak Penelitian ini mengkaji perkembangan Islam dalam masyarakat Banjar, dengan fokus pada aspek budaya dan fiqh tasawuf. Masyarakat Banjar merupakan masyarakat yang kaya budaya dan sangat dipengaruhi oleh tradisi Islam. Tradisi Islam mewarnai setiap tahap kehidupan dalam masyarakat Banjar, yang terlihat dalam berbagai ritual kehidupan seperti kelahiran, pengasuhan anak, pendidikan, masa remaja, persiapan pernikahan, pernikahan, pendidikan agama, kondisi sakit, dan kematian. Selain itu, tradisi Islam juga diamati selama perayaan hari besar agama seperti Ramadhan, Syawal, Idul Adha, dan Haji.Tradisi Islam yang masuk ke masyarakat Banjar sangat dipengaruhi oleh ajaran tasawuf yang diperkenalkan oleh ulama Islam dari Timur Tengah. Pada tahap berikutnya, beberapa ulama besar dari Banjar pergi ke Timur Tengah untuk mempelajari ilmu pengetahuan Islam dan menyebarkan pengetahuan mereka dengan mengajar dan menerbitkan kitab-kitab untuk menyebarkan ajaran Islam.Salah satu ulama Banjar yang terkenal adalah Syeikh Arsyad Al-Banjari, yang telah meluruskan kembali budaya Banjar sesuai dengan ajaran Islam dengan melarang praktik seperti Sanggar Banua dan Membuang Pasilih, yang dapat menyeret masyarakat Banjar menuju kemungkaran dan bid'ah dhalalah, termasuk praktik memberi makan orang ghaib. Kata Kunci: Perkembangan Islam, Masyarakat Banjar, Pengaruh Budaya, Fiqh Tasawuf, Ritual Kehidupan, Tradisi Islam, Ulama Timur Tengah, Syeikh Arsyad Al-Banjari.